Validity of predictive equations for estimation of resting energy expenditure among mechanically ventilated critically ill patients: Preliminary findings - Tah, Pei Chien; Hakumat-Rai, Vineya-Rai; Poh, Bee Koon; Mat Nor, Mohd Basri; Abdul Majid, Hazreen; Kee, Chee Cheong; Kamarul Zaman, Mazuin; Hasan, Mohd Shahnaz (2017)
Background: Several predictive equations (PEs) have been developed for estimation of energy requirement but very few has been validated among mechanically ventilated critically ill patients in Asian population. Objectives: This study aimed at determining the validity of 14 PEs for energy requirement and identifying metabolic determinants that influence resting energy expenditure (REE). Methods: REE was measured among 90 ventilated critically ill patients by using IndirectCalorimetry (IC). 14 PEs used to estimate patients’ energy requirement was validated against IC using intraclass correlation coefficient (ICC) test. Metabolic determinants assessed were sex, body mass index (BMI), age, patient condition, mNUTRIC score and body cell mass (BCM) status. Recruitment is on-going until sample size of 314 is achieved. Results: In the early phase (≤5days), mean REE for all critically ill patients was 1677±403kcal whereas for obese patients was 1926±438kcal. Penn State equation [PSU(m),2003b] shows highest correlation (ICC=0.635), 95%CI(0.49,0.75), p<0.001 with IC in estimating REE among all critically ill patients. Meanwhile, Harris Benedict Equation (variants) [HBEa(50)x1.25] shows highest correlation (ICC= 0.581), 95%CI(0.12,0.84), p=0.010 in estimating REE among obese patients. There was significant difference in REE by sex, BMI and BCM status during early and late phase (6-10days). During chronic phase (>10days), significant difference in REE was observed in patient condition and BCM status. Conclusion: These preliminary results show that most available validated equations had poor to fair agreement with IC measurement. As such, we opine that it is crucial to determine a reliable PE for assessing energy requirement of Asian critically ill patients.